Neate: Bank Confidentiality - Griffiths, Gwendoline; Neate, F. W. (Haywards Heath, West Sussex : Tottel Pub. : International Bar Association, 2006)
Published in conjunction with the International Bar Association, this new, fully revised fourth edition provides a clear picture of the laws relating to bank confidentiality. Each chapter sets out the basic rules of confidentiality - the nature, extent and source of those rules - and examines their civil and criminal nature, the remedies available for breach of those obligations and the extent to which conflicts of interest arise and how data protection legislation operates in relevant jurisdictions. Each contributor then analyses these issues in the light of statutory and non-statutory frameworks of civil and criminal law in their jurisdiction. New chapters include coverage of the Cayman Islands, China and International Anti-Money Laundering initiatives.
Includes Index.
rpm 05/09/12
Loans
Keywords: Confidential communications -- Banking -- Cross-cultural studies; Banks and banking -- Records and correspondence -- Law and legislation -- Cross-cultural studies; Financial disclosure -- Law and legislation -- Cross-cultural studies